Mortality Decline, Impatience and Aggregate Wealth Accumulation with Risk-Sensitive Preferences - Antoine Bommier (ETH Zurich, CER-ETH - Center of Economic Research, 2014)
The paper discusses the impact of longevity extension on aggregate wealth accumulation, accounting for changes in individual behaviors as well as changes in population age structure. It departs from the stan- dard literature by adopting risk-sensitive preferences. Human impatience is then closely related to mortality rates and aggregate wealth accumula- tion appears to be much more sensitive to demographic factors than usually found. Illustrations are provided using historical mortality data from dif- ferent countries.
Keywords: J1; E21; D91; 330; longevity; life-cycle savings; wealth accumulation; risk-sensitive preferences; risk aversion